Effects of glycine on cell growth and pigment biosynthesis in Rhodobacter azotoformans. (23rd November 2020) - Yue, Huiying; Zhao, Chungui; Yang, Suping; Jia, Yaqiong
Abstract: The effect of exogenous glycine (a precursor for the biosynthesis of bacteriochlorophyll) on the cell growth and photopigment accumulation was investigated in phototrophic growing Rhodobacter azotoformans 134K20. The growth rate and the biomass of strain 134K20 were significantly inhibited by glycine addition when ammonium sulfate or glutamate were used as nitrogen sources and acetate or succinate as carbon sources. A characteristic absorption maximum at approximately 423 nm was present in the absorption spectra of glutamate cultures while it was absent by the addition of high‐concentration glycine of 15 mM. The component account for the 423 nm peak was eventually identified as magnesium protoporphyrin IX monomethyl ester, a precursor of bacteriochlorophyll a (BChl a ). Comparative analysis of pigment composition revealed that the amount of BChl a precursors was significantly decreased by the addition of 15‐mM glycine while the BChl a accumulation was increased. Moreover, glycine changed the carotenoid compositions and stimulated the accumulation of spheroidene. The A 850 / A 875 in the growth‐inhibited cultures was increased, indicating an increased level of the light‐harvesting complex 2 compared to the reaction center. The exogenous glycine possibly played an important regulation role in photosynthesis of purple bacteria.